On an invariant set in the heat conductivity problem with time lag - Tukhtasinov, Muminjon; Ibragimov, Gafurjan I.; Mamadaliev, Numanjon O. (Hindawi Publishing Corporation, 2013)
The problems of weak and strong invariance of a constant multivalued mapping with respect to the heat conductivity equation with time lag are studied. Sufficient conditions of weak and strong invariance of a given multivalued mapping are obtained.